A 13.56 MHz Localization System Utilizing a Switched Injection Locked Transponder - Kirsch, Fabian; Vossiek, Martin; Schäfer, Tobias (IEEE Conference on Microwaves, Communications, Antennas and Electronic Systems (COMCAS) 2009, 2009)
In this paper a low-frequency local positioning system at 13.56 MHz is presented. The system is aiming at short range indoor localization problems, where a measurement through a crowd of people is required. Indoor navigation or information systems e.g. in museums, public buildings or fairs are possible applications. With a wavelength of approx. 22 m the system operates in the near field. Ranging is accomplished by measuring the phase shift between a transmitted CW base station signal and a response generated in the transponder with the use of the novel switched injection locked oscillator concept. First measurement results prove that the proposed concept allows for robust indoor ranging with an accuracy in the decimeter-rang
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.a1356m
Keywords: Locked oscillators; Phase measurement; Transponders; Voltage controlled oscillators

A Distance-Bounding Concept for Bilateral IEEE 802.15.4 Communication - Wittwer, J.; Kirsch, Fabian; Vossiek, Martin (IEEE Conference on Microwaves, Communications, Antennas and Electronic Systems (COMCAS) 2009, 2009)
In this paper a concept for bounding the operation range of IEEE 802.15.4 based wireless sensors is introduced. The distance-bounding is based on a signal round-trip time of flight measurement. For the round-trip time of flight measurement two essential problems have to be solved: on the one hand the time of arrival estimation and on the other hand precise clock synchronization. In our novel approach both challenges were solved by utilizing the preamble and start of frame delimiter (SFD) signal that is available in every IEEE 802.15.4 data package. Based on a Wiener optimal filter applied to the demodulated received IEEE 802.15.4 packet the time of arrival is estimated. The frequency offset is estimated based on the residual frequency of the undemodulated received signal. Exemplary indoor measurements with a system based on a TI CC2430 ZigBEE-Chip prove that the introduced concept allows for a distance-bounding accuracy of approx. 1 m in indoor scenarios with moderate multipath distortion
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.adista
Keywords: Distance bounding; Distance measurement; Frequency estimation; IEEE 802.15.4; Wiener filtering

Advanced Wireless Local Positioning via Compressed Sensing - Kirsch, Fabian; Gottinger, Michael; Dobrev, Yassen; Vossiek, Martin (IEEE Access, 2018)

A local TX coil for 3T shoulder imaging - Kirsch, Fabian; Schöpfer, Johanna; Huber, Klaus; Biber, Stephan; Martius, Siegfried (2014)

Analytical Study about the Impact of Multipath Propagation on UHF-RFID Ranging Techniques - Kirsch, Fabian; Miesen, Robert; Vossiek, Martin (IEEE International Conference on Wireless Information Technology and Systems 2012, 2012)
Given the narrow bandwidth of UHF-RFID it is not possible to separate the different signal paths apart. In this paper the SNR was derived, necessary for any nonlinear super-resolution algorithms. As long as these SNR levels are not met, any evaluation method will give a weighted mean of all the individual paths that exist in the perceived channel. Evaluation methods that use only one of 'RSSI' and 'phase' will even be worse. In order to open the possibilities of multipath resistant single-antenna ranging to the field of UHF-RFID applications new regulations or technologies with greater bandwidths are unavoidable. © 2012 IEE
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.analyt

A new 140 GHz planar diode finline mixer for radiometer applications - Kirsch, Fabian; Boheim, M.; Schmidt, L.; Ritter, J.; Brankovic, V.; Bayer, R.; Arndt, F.; Klein, U.; Künzi, K.; Schwab, G.; Crowe, TW. (1994)

A Novel Method for UHF RFID Tag Tracking Based on Acceleration Data - Parr, Andreas; Miesen, Robert; Kirsch, Fabian; Vossiek, Martin (6th Annual IEEE International Conference on RFID (IEEE RFID 2012), 2012)
Options for RFID tag tracking and localization are an essential asset for future high performance RFID reader systems. A reader with long reading range, high reading rate and multi-tag capability should be able to assist the user to find / retrieve tags, to create spatial object maps and to restrict the reading range to specific regions of interest. In this paper we introduce a novel method for RFID tag tracking with a moving for example handheld reader. An inertial measurement unit (IMU) is used to characterize the handheld trajectory. Contrary to approaches where IMU locations are reconstructed via double integration of the acceleration data, our novel technique only uses acceleration data without knowledge of the actual antenna locations. Inexpensive, standard inertial sensors can be used in this approach, and the usual drift and offset issues associated with IMU-based positioning are avoided. Parallel to the IMU acceleration data, the phase of the backscattered RFID signal is input. Double differentiation of the signal phase yields a second acceleration data set. By comparing the IMU and the RFID signal phase acceleration data, the direction of arrival of the RFID signal is estimated using a quasi-spatial optimal filter. This paper introduces the novel RFID tracking approach and illustrates its capability with numerical simulations and experimental results. This novel approach is a simple, yet promising, solution which can be implemented in any handheld reader and will improve its functionality considerably. © 2012 IEE
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.anovel_8
Keywords: angle of arrival; phase measurement; UHF RFID

An X-band phased array microwave/photonic beamforming network - Kirsch, Fabian; Banerjee, S.; Zimmer, G.; Feldle, H.; Marten, P.; Schmidt, Lorenz-Peter (1993)

Application of the Principal Component Analysis for acceleration based UHF RFID tag tracking - Parr, Andreas; Miesen, Robert; Kirsch, Fabian; Vossiek, Martin (IEEE International Conference on Wireless Information Technology and Systems 2012, 2012)
An algorithm for AoA estimation of UHF RFID tags, based on an acceleration defined synthetic aperture is derived with the aid of the Principal Component Analysis. It gives an analytical solution for the tag direction and requires significantly less computational effort than comparable algorithms while performing nearly as good as the benchmark algorithm. Handheld tracking systems using the proposed algorithm could therefore be implemented with significantly higher cost and power efficiency. © 2012 IEE
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.applic_8

Are odorant constituents of herbal tea transferred into human milk? - Denzer, Melanie; Kirsch, Fabian; Büttner, Andrea (Journal of Agricultural and Food Chemistry, 2015)

A wireless crane to vessel locating system for sea swell compensation - Nikolaiev, Anton; Kirsch, Fabian; Vossiek, Martin; Shu, Xinyu; Bohn, Christian; Duden, Heinrich (2014 20th International Conference on Microwaves, Radar and Wireless Communications, MIKON 2014, 2014)
Sea swell causes significant risk in transferring people and material to offshore constructions and oftentimes hamper the accessibility completely. The weather window where a construction is accessible can be enlarged notably if a crane is equipped with a sea swell compensation system. For a crane to vessel swell compensation system it is required to measure the 3D position of the crane load handling device relative to the deck of ship precisely, reliably and in real-time. In this paper a novel wireless crane to vessel locating system is introduced. Several secondary radar units that are mounted on the ship deck are measuring the distance to a responder unit attached to the crane boom. The 3D localization is based on a fusion of secondary radar distance measurements and the data from an inertial sensor platform. The fusion is done by a quaternion based extended Kalman filter which implements both multilateration and strapdown inertial navigation techniques. Real measurement data acquired with the inertial platform on a ship and radar data measured with the realized local positioning radar onshore are fed in a PC based simulation of the complete system. The real data simulations prove that the developed real time locating system provides the required position information precisely and reliably. By this it is shown that the novel wireless locating system is well suited for sea swell compensation equipment.
Keywords: inertial navigation; Kalman filter; Radar position measurement; radio navigation; swell compensation

Clock Synchronization in Wireless Positioning and Sensor Networks - Kirsch, Fabian; Vossiek, Martin (IEEE Radio & Wireless Symposium, Workshop on Radar and positioning systems: innovative approaches and future trends, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.clocks

Coherent Automotive Radar Networks: The Next Generation of Radar-Based Imaging and Mapping - Gottinger, Michael; Hoffmann, Marcel; Christmann, Mark; Schütz, Martin; Kirsch, Fabian; Gulden, Peter; Vossiek, Martin (IEEE Journal of Microwaves, 2021)
Imaging radar is a key perception technology for automotive and industrial applications. A lot of progress has been made with high channel count systems, deploying, for example, 12 transmit and 16 receive channels with cascaded monolithic microwave integrated circuit solutions. Nevertheless, fully automated driving requires even higher angular resolution for drive-under/drive-over decisions and exact predictions of object trajectories in dense urban driving scenarios. Both problems can be solved by increasing the antenna size and building larger radars. However, there is a physical limit to what can be placed on the front of a car, and manufacturing very large arrays is quite difficult. Thus, coherent automotive radar networks are a way to achieve high spatial resolution and obtain the complete velocity vector of an object from a single measurement. This solution is commercially attractive, as the sensor can remain relatively small, and complexity can be moved from the physical hardware to algorithms and processing. Two different test setups, each comprised of two multiple-input multiple-output radar units in the 76–77 GHz band, are presented in this article. To obtain azimuth and additional elevation information, the setups use a 1D and a 2D antenna array, respectively. Processing-based coherent evaluation is employed to create an additional radar image with doubled azimuth resolution and improved signal-to-noise ratio and to enable the estimation of vectorial target velocities. These benefits are presented and compared with optical reference images in traffic scenario

Coherent Full-Duplex Double-Sided Two-Way Ranging and Velocity Measurement Between Separate Incoherent Radio Units - Gottinger, Michael; Kirsch, Fabian; Gulden, Peter; Vossiek, Martin (IEEE Transactions on Microwave Theory and Techniques, 2019)
This paper presents a novel coherent full-duplex(FD) double-sided two-way ranging (CFDDS-TWR) techniquefor wireless locating and velocity measurement between separateradio units. The idea presented here is a quantum leap inwireless locating since it enables coherent ranging, continuousphase tracking, and velocity measurement between wirelessunits that operate incoherently with separate low-cost crystaloscillator clock sources. Frequency modulated continuous wavechirp sequences are exchanged in a FD manner between tworadio units. The signals transmitted from two radio units arereceived, respectively, by each of the two units and down-converted in a mixer with the receiver’s own transmit signalto generate a beat signal in each unit. The two beat signalsare then processed together, after one beat signal is transmittedto the partner unit. Phase coherent range and Doppler phasemeasurements can be conducted between incoherent radio units.The presented CFDDS-TWR technique also offers options forreducing noise-like distortions caused by mixing the productsof uncorrelated phase noise. We show both analytically andexperimentally that the described compensation method reducesthe noise level and enhances the dynamic range of the ranging sig-nals tremendously—as evidenced by an improvement of around24 dB in our results. These unique signal and synchronizationproperties show that the CFDDS-TWR method is a highlyaccurate measurement approach. Results acquired with a 24-GHztest system in a 7- to 17-m range demonstrate a standarddeviation in range and velocity of 0.25 mm and 0.05 mm/s,respectivel
Keywords: Wireless communication; Chirp; Clocks; Synchronization; Doppler radar; Distance measurement; Doppler radar; full-duplex (FD); phase measurement; phase noise (PN); radar; radio navigation; synchronization; transponders; wireless localization

Distributed Kalman Filter for Precise and Robust Clock Synchronization in Wireless Networks - Kirsch, Fabian; Vossiek, Martin (IEEE Radio & Wireless Symposium, 2009)
A novel concept for robust and precise clock synchronization in wireless networks is introduced. The concept is based on a Kalman filter that is parallelly distributed on all network nodes. Each node uses the state estimates of other nodes to determine a local estimate of the global clock. A voting algorithm that evaluates the state estimates of several nodes is used to adjust the virtual global clock master. By avoiding any physical central clock master the distributed global clock is extremely tolerant of single nodes malfunction and no single points of failure exist in the network and protocol. In experiments with an IEEE 802.15.4 (ZigBee-PHY) network it was shown that even with a packet loss of 75% the achieved clock synchronization was always better than 4 μs. Another advantage of the realized protocol is that it requires only very low basic data traffic. Thus, the concept is ideally suited for time-synchronized sensor networks, ad hoc networks, or wireless time-triggered realtime systems. ©2009 IEEE.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.distri
Keywords: Kalman filtering; Networks; Radio communication; Synchronization

Hybrid RFID System-based Pedestrian Localization: A Case Study - Wang, Haowei; Bauer, Georg; Kirsch, Fabian; Vossiek, Martin (10th Workshop on Positioning, Navigation and Communication 2013 (WPNC 2013), 2013)
Localization systems using RFID - especially passive RFID - are coming increasingly under the spotlight. Passive RFID has a relatively small sensing range compared to other radio-frequency-based localization techniques. Therefore in practice the deployed tags may not cover the whole scene of interest. Additionally, in the area of pedestrian localization, the unpredictable movement of pedestrians makes a complete RFID tag coverage extremely difficult. This paper introduces a hybrid RFID localization system used for indoor pedestrians to overcome the coverage shortfall associated with passive RFID tags. Two extra sources are used to assist the RFID system: local INS sensors and ZigBee nodes. A particle filter serves as a fusion framework. A test scenario was built with 220 RFID tags and 8 ZigBee nodes deployed in a museum. Different algorithms were evaluated in this deployment. The results show that the hybrid approach produces robust localization even with a low number of tags. © 2013 IEE
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.hybrid
Keywords: dead reckoning; fingerprinting; hybrid localization; particle filter; RFID

Localization of Standard Compliant Passive RFID Transponders - Miesen, Robert; Kirsch, Fabian; Vossiek, Martin (RFIC 2013 Workshop on Radio Frequency Systems for Indoor Localization, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.locali

Moeglichkeiten, Grenzen und Anwendungsbeispiele der drahtlosen und energieautarken Sensorik - Vossiek, Martin; Kirsch, Fabian (Mikrosysteme und Energie - von der Planung bis zur Fertigung, 2012)
lhft_intern.bib::Vossiek2012zempro

Neuartige Verfahren zur Holographische Ortung von UHF RFID Tags - Miesen, Robert; Kirsch, Fabian; Vossiek, Martin (RADCOM 2011 - Workshop, Developer Forum and Exhibition, 2011)
lhft_intern.bib::Miesen2011b

Optimization of Fusion Algorithm for Hybrid Pedestrian Localization and Navigation - Wang, Haowei; Bauer, Georg; Kirsch, Fabian; Vossiek, Martin (9th Workshop on Positioning, Navigation and Communication 2012 (WPNC 2012), 2012)
Hybrid pedestrian localization based on multiple data sources is becoming more and more popular. Nevertheless, accurate and reliable pedestrian localization is still a challenge due mainly to their unpredictable movement. For some applications such as interactive museum guidance unpredictable pedestrian movement is a major obstacle to accurate localization. In this paper we introduce a novel fusion algorithm using best-neighbor rating. The algorithm reduces the accumulated error originating from unreliable sensor measurements and increases the efficiency by only evaluating the nearby cells of the last estimated position. Experimental results show that a mean error of less than 1.5 M is achievable in real-world scenarios. © 2012 IEE
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.optimi
Keywords: Dead Reckoning; Inertial Sensor; Localization; Navigation; Sensor Fusion; ZigBee

Phase based multi carrier ranging for UHF RFID - Miesen, Robert; Kirsch, Fabian; Gröschel, Patrick; Vossiek, Martin (IEEE International Conference on Wireless Information Technology and Systems 2012, 2012)
The different methods to process phase measurement data of a MFCW ranging system with their characteristics are well suited to be used for UHF RFID ranging. Our measurements show that ranging ISO 18000-6C UHF RFID tags under FCC regulations is possible in outdoor conditions despite the limited bandwidth. Our next steps will be to further compare the robustness of the algorithms and to conduct measurements in multipath environments. Additionally we will combine this approach with other localization techniques. Using multiple antennas or synthetic apertures, this approach can help to increase the radial resolution significantl
lhft_intern.bib::Miesen2012a

Precise local-positioning for autonomous situation awareness in the Internet of Things - Kirsch, Fabian; Miesen, Robert; Vossiek, Martin (2014 IEEE MTT-S International Microwave Symposium, IMS 2014, 2014)
This paper reviews different wireless local positioning principles and explains the interaction between local positioning and the Internet of Things (IOT). The principle, performance and use of recent local positioning systems in the context of the IOT are shown in detail for typical applications. The first application is the accurate real-time localization of transportation vehicles using local positioning radar. The second application is the loading state characterization of goods in the proximity of a forklift enabling fully automated warehouse management. The third application is the dynamic localization of UHF-RFID tags with a handheld reader, which provides helpful augmented reality for logistics personnel. The final application is the real-time localization of tools for production monitoring. The developed ultrawideband (UWB) locating system is based on a pulsed frequency modulated continuous wave (FMCW) radar principle. By using assisting inertial sensors and advanced fusion algorithms, highly accurate 3D localization was achieved even in complex industrial environments with dense multipath channels and shadowing. © 2014 IEEE.
Keywords: FMCW; internet of things; position measurement; radar applications; radar tracking; RFID tags; transponder; wireless sensor networks

Radar based localisation of tools in production szenarios - Kirsch, Fabian; Vossiek, Martin (Workshop on "Microwave Sensors & Sensor Systems," 6th German Microwave Conference (GeMiC) 2011, 2011)
lhft_intern.bib::Kirsch2011

UHF RFID Localization Based on Synthetic Apertures - Miesen, Robert; Kirsch, Fabian; Vossiek, Martin (IEEE Transactions on Automation Science and Engineering, 2013)
Reading ranges are being extended in the wake of recent advances in UHF radio frequency identification (RFID) systems, and with the advent of larger reading ranges, tag localization has moved into the spotlight. Recently, we introduced a new UHF RFID tag localization technique. The proposed method is based on phase measurements taken along a synthetic aperture. A holographic image is calculated based on the scanned phase values. The image represents the spatial probability density function for the actual tag location. This paper presents this innovative method in detail. Simulations that illustrate the effect of the given trajectory are included. Extensive measurements obtained in a reflective lab environment are presented. We discuss the method's effectiveness with respect to measurement errors, antenna phase center distortions, and the available phase information. The results show the potential practical applications for the method in moving reader antennas, such as handheld readers or readers mounted on vehicles like forklifts or mobile robotic systems. © 2012 IEEE.
UnivIS-Import:2015-03-09:Pub.2013.tech.IE.LEH.uhfrfi
Keywords: Holography; Image reconstruction; Position measurement; Radio frequency identification (RFID); Radio navigation; Synthetic aperture radar; Transponders

Untersuchungen zur Energieversorgung Eines Systems zur Drahtlosen Datenübertragung für Anwendungen in der Medizin - Kirsch, Fabian; Wittwer, J. (2008)

Untersuchungen zur Energieversorgung eines Systems zur drahtlosen Datenübertragung für Anwendungen in der Medizin - Wittwer, J.; Kirsch, Fabian; Vossiek, Martin (Sensoren und Messsysteme 2008, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.unters

Where is the Tag? - Miesen, Robert; Ebelt, Randolf; Kirsch, Fabian; Schäfer, Tobias; Li, Gang; Wang, Haowei; Vossiek, Martin (IEEE Microwave Magazine, 2011)
Radio-frequency identification (RFID) localization developments and trends are reviewed. RFID localization relative to a reader can be broken down into two different tasks: ranging and direction finding. A system with both of these capabilities can provide two-dimensional (2-D) or three-dimensional (3-D) localization and an RFID system with only one of these capabilities can still provide useful functionalities. Standard RFID systems feature only coarse locating capabilities with a granularity given by the dimension of a cell formed by a reader. RFID ranging techniques may be categorized according to three criteria. The first and second are the type of transponder and the fundamental principle behind tag localization. Broadband chipless RFID tags have emerged as very promising candidates for next generation locatable RFID transponder
lhft_intern.bib::Miesen2011c

Wireless Local-Positioning Systems for Online Monitoring - Kirsch, Fabian; Miesen, Robert; Vossiek, Martin (IEEE RWW Workshop on Machine-To-Machine (M2M) Communication at IEEE Radio Wireless Week 2013, 20-23 Jan., 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.wirele